PENERAPAN MODEL PEMBELAJARAN RME BERBASIS ETHNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MAHASISWA CALON GURU PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS BENGKULU - Octizasari, Ginta; Haji, Saleh (JUPITEK : Jurnal Pendidikan Matematika, 2018)
This study aims to apply the RME-based ethnomatematics learning model to improve problem solving skills of prospective mathematics education teachers at the University of Bengkulu. This research is Classroom Action Research (CAR) with data collection techniques through student observation sheets and learning outcomes tests. Subjects in this study were 2A semester students at the University of Bengkulu in the 2017/2018 school year, totaling 22 people consisting of 6 male students and 16 female students. This study lasted two cycles through the RME-based ethnomatematics learning model with the following phases (1) orienting students to problems; (2) organizing students to study; (3) assisting independent and group investigations; (4) develop and present artifacts (works); (5) process analysis and evaluation. Based on this research, it was concluded before the implementation of the Ethnomatematics-based RME learning model, pre-action tests were conducted which resulted in an average value of 69.00 after the implementation of the ethnomatematics-based RME learning model could improve students' mathematical problem-solving ability with the problem solving ability test results. mathematics students get an increase in the average value of the first cycle of 70.77 to the second cycle of 79.59 and the percentage of mathematical problem solving ability increased from the first cycle of 81.82% to the second cycle of 95.45%